Recent selection of candidate genes for mammal domestication in Europeans and language change in Europe: a hypothesis - Antonio Benítez-Burraco; Evgeny Chekalin; Sergey Bruskin; Tatiana Tatarinova; Irina Morozova (Taylor & Francis Group, 2021)
Background and aim Human evolution resulted from changes in our biology, behaviour, and culture. One source of these changes has been hypothesised to be our self-domestication (that is, the development in humans of features commonly found in domesticated strains of mammals, seemingly as a result of selection for reduced aggression). Signals of domestication, notably brain size reduction, have increased in recent times. Methods In this paper, we compare whole-genome data between the Late Neolithic/Bronze Age individuals and modern Europeans. Results We show that genes associated with mammal domestication and with neural crest development and function are significantly differently enriched in nonsynonymous single nucleotide polymorphisms between these two groups. Conclusion We hypothesise that these changes might account for the increased features of self-domestication in modern humans and, ultimately, for subtle recent changes in human cognition and behaviour, including language.